2001
DOI: 10.1103/physreva.65.012712
|View full text |Cite
|
Sign up to set email alerts
|

Rb-Xe spin relaxation in dilute Xe mixtures

Abstract: We present measurements of spin-relaxation of Rb atoms in He(98%)-N 2 (1%)-Xe(1%) mixtures similar to those used in magnetic resonance imaging polarizers. The pressure dependence allows us to separate out contributions from Rb-Xe van der Waals molecules and binary collisions. For the first time, we observe the predicted increase in the molecular contribution at high pressure. Our data suggest that the deduced molecular breakup rate has a strong temperature dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 19 publications
2
35
1
Order By: Relevance
“…For example, ongoing simulations predict a high Γ SD value of ∼134,300 s −1 for the experimental conditions of the 65°C data in Fig. 2, dominated by Xe collisions (25)(26)(27). However, the high resonant photon flux at the front of the cell should give nearly a ninefold greater optical pumping rate (γ OP ∼ 1.16 × 10 6 s −1…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…For example, ongoing simulations predict a high Γ SD value of ∼134,300 s −1 for the experimental conditions of the 65°C data in Fig. 2, dominated by Xe collisions (25)(26)(27). However, the high resonant photon flux at the front of the cell should give nearly a ninefold greater optical pumping rate (γ OP ∼ 1.16 × 10 6 s −1…”
Section: Discussionmentioning
confidence: 93%
“…where γ OP (r) is the local OP rate [given by the integrated product of the laser flux and the Rb absorption cross-section (31)], and Γ SD is the Rb electronic spin destruction rate, which is dominated by nonspin-conserving collisions with Xe [via the spinrotation interaction (25,27)] and is high under our conditions because of its proportionality to [Xe]. Correspondingly, the laser power used here is also high-usually ∼170 W, mostly resonant with the Rb D 1 line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since spin destruction due to Van der Waals molecules is so complex that exact value is hard to obtain, we use R vdW ≈ 3240 Hz for an estimate. 18 For spherical cell without anti-relaxation coating R wall can be expressed as,…”
Section: A Single Frequency Lasermentioning
confidence: 99%
“…al. measured this rate in the "short lifetime" region [23] (total gas pressure on the order of an amagat). They reported that with a gas mixture of 1% Xe, 1% N 2 and 98% He, the vdW spin destruction rate is 2049 s −1 at 150 • C and 3240 s −1 at 80 • C. These rates are independent of the total gas pressure, but dependent on the gas composition.…”
Section: Rb Spin Destruction Ratementioning
confidence: 99%